1997
DOI: 10.1038/bjc.1997.488
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant i.v. and oral clodronate in the relief of bone pain – a double-blind placebo-controlled study in patients with prostate cancer

Abstract: Summary Fifty-seven patients with advanced prostate cancer resistant to first-line hormonal therapy were treated with estramustine and additionally randomized for treatment with clodronate or placebo. Clodronate treatment was started with 5 days intravenous administration (300 mg day-') and followed by oral treatment (1.6 g day-1) for 12 months. Skeletal pain relief was only about 10% better in the clodronate than in the placebo group. The results do not support the superiority of combined intravenous and oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 12 publications
0
38
0
1
Order By: Relevance
“…Of these 31 studies, 6 reported on bone metastases from breast cancer, [71][72][73][74][75][76] 13 reported on bone metastases from prostate cancer [77][78][79][80][81][82][83][84][85][86][87][88][89] and 12 reported on bone metastases from OSTs. [90][91][92][93][94][95][96][97][98][99][100][101] Of the remaining eight studies that did contribute data to the network meta-analyses, four reported breast cancer 31,[102][103][104] [18 reports 22,31,[102][103][104][105][106][107][108][109][110][111][112][113][11...…”
Section: Number and Type Of Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 31 studies, 6 reported on bone metastases from breast cancer, [71][72][73][74][75][76] 13 reported on bone metastases from prostate cancer [77][78][79][80][81][82][83][84][85][86][87][88][89] and 12 reported on bone metastases from OSTs. [90][91][92][93][94][95][96][97][98][99][100][101] Of the remaining eight studies that did contribute data to the network meta-analyses, four reported breast cancer 31,[102][103][104] [18 reports 22,31,[102][103][104][105][106][107][108][109][110][111][112][113][11...…”
Section: Number and Type Of Studies Includedmentioning
confidence: 99%
“…158 (61) 159 (64) ECOG status, n (%) 1 or less 211 (83) 215 (87) 2 or more 42 (17) 32 (13) Missing 4 (>1)…”
Section: Fizazi 2011mentioning
confidence: 99%
“…The changes in BMD and reductions in spinal fracture rates were similar to those published in the fracture intervention trials using alendronate for postmenopausal osteoporosis. 60 Role of bisphosphonates in the prevention of bone loss in men with prostate carcinoma who are receiving ADT Etidronate, clodronate, pamidronate, and zoledronic acid have been studied recently in men with prostate carcinoma to assess their ability in inhibiting hypogonadal-induced bone loss, 4,[11][12][13]19,45,46 treating refractory metastatic bone pain, [61][62][63] and preventing the skeletal-related events associated with metastatic disease. 46 It is important to note that the dosage regimens of the various bisphosphonates differ significantly according to their desired antitumor or antiosteoporotic effects, with more frequent infusion rates required to reduce skeletal-related endpoints.…”
Section: Data From Randomized Controlled Trials In Men Without Prostamentioning
confidence: 99%
“…There were initially rather fewer studies in the prostate cancer setting, although some early work showed reductions in bone pain with clodronate, 43,44 although this was not later borne out in randomised studies with this drug. 45,46 Early small-scale studies with pamidronate provided encouraging signs of its potential benefit, 47,48 but it was several years before a well-designed randomised study was published on the use of later-generation bisphosphonates in prostate cancer.…”
Section: Current Treatment Options For Bone Metastasesmentioning
confidence: 99%